Manažerská etika - Dytrt, Zdeněk (Univerzita Pardubice, 2000)
Manager's ethics could be the inovation in the practical management. It concerns not only development of technique in management, but also requires the development of inovation of the manager's worksystem.
Keywords: Management; manažerská etika; řízení; morálka; Podnikání; veřejná správa